PDR Transporter ABC1 Is Involved in the Innate Azole Resistance of the Human Fungal Pathogen Fusarium keratoplasticum - James, Jasper Elvin; Lamping, Erwin; Santhanam, Jacinta; Cannon, Richard David (Frontiers in Microbiology, 2021)
Fusarium keratoplasticum is arguably the most common Fusarium solani species complex (FSSC) species associated with human infections. Invasive fusariosis is a life-threatening fungal infection that is difficult to treat with conventional azole antifungals. Azole drug resistance is often caused by the increased expression of pleiotropic drug resistance (PDR) ATP-binding cassette (ABC) transporters of the ABCG sub-family. Most investigations of Fusarium ABC transporters associated with azole antifungal drug resistance are limited to plant pathogens. Through the manual curation of the entire ABCG protein family of four FSSC species including the fully annotated genome of the plant pathogen Nectria haematococca we identified PDR transporters ABC1 and ABC2 as the efflux pump candidates most likely to be associated with the innate azole resistance phenotype of Fusarium keratoplasticum. An initial investigation of the transcriptional response of logarithmic phase F. keratoplasticum cells to 16 mg/L voriconazole confirmed strong upregulation (372-fold) of ABC1 while ABC2 mRNA levels were unaffected by voriconazole exposure over a 4 h time-period. Overexpression of F. keratoplasticum ABC1 and ABC2 in the genetically modified Saccharomyces cerevisiae host AD∆∆ caused up to ~1024-fold increased resistance to a number of xenobiotics, including azole antifungals. Although ABC1 and ABC2 were only moderately (20% and 10%, respectively) expressed compared to the Candida albicans multidrug efflux pump CDR1, overexpression of F. keratoplasticum ABC1 caused even higher resistance levels to certain xenobiotics (e.g. rhodamine 6G and nigericin) than CDR1. Our investigations suggest an important role for ABC1 orthologs in the innate azole resistance phenotype of FSSC species.